PENERAPAN KEUANGAN BERKELANJUTAN DAN TINGKAT KEPATUHAN LAPORAN KEUANGAN BERKELANJUTAN BANK DI INDONESIA - Yulianto, Tomi; Prabowo, Hayu Susilo (Journal of Accounting, Management and Islamic Economics, 2024)
This study aims to assess the completeness and suitability of the Sustainable Financial Statement in Conventional and Sharia Banks with reporting principles, disclosure standards and overall assessment of the implementation of Peraturan OJK (POJK) Nomor 51 tahun 2017 on Implementation of Sustainable Finance for Financial Service Institutions, Issuers, and Public Companies. The research method of this study is an analysis of the Banks’ Yearly Sustainable Financial Statement in the period 2016-2018 and then performed a qualitative analysis based on completeness of 86 components fulfillment in 43 variables designated in the reporting technical guidelines which is regulated by OJK and reporting quality assessment. The result of the test shows the improvement in both the completeness and quality of the Sustainable Financial Statement. Conventional Banks conduct the reporting relatively better compared to Sharia Bank. In general, Banks are accountable in the report, especially on the disclosure of the efficiency of resources and energy use. The difference that is reflected in the report between Conventional and Sharia banks that have financial conglomerate relations needs to be a concern for the stakeholders including regulators to include sustainable finance as part of financial conglomerates and reporting principles needs to be standardized in the form of report format or indexing by regulator.